2018
DOI: 10.1074/jbc.m117.816793
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function analyses unravel distinct effects of allosteric inhibitors of HIV-1 integrase on viral maturation and integration

Abstract: Recently, a new class of HIV-1 integrase (IN) inhibitors with a dual mode of action, called IN-LEDGF/p75 allosteric inhibitors (INLAIs), was described. Designed to interfere with the IN-LEDGF/p75 interaction during viral integration, unexpectedly, their major impact was on virus maturation. This activity has been linked to induction of aberrant IN multimerization, while inhibition of the IN-LEDGF/p75 interaction accounts for weaker antiretroviral effect at integration. Since these dual activities result from I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 53 publications
2
51
0
Order By: Relevance
“…242). Because Asn is often found at position 124 and A124D conferred significant resistance to the quinoline ALLINI BI-D (165), recent studies have tested antiviral activities of compounds against HIV-1 strains harboring representative 124/125 polymorphisms, such as Thr/Thr, Thr/ Ala, Ala/Thr, Ala/Ala, Asn/Thr, and Asn/Ala (200,207,215). Whereas Asn-124 and Ala-125 each conferred ϳ50-fold resistance to pyridine ALLINI compound 20 (200) and thiophene ALLINI MUT-A (215), respectively, naphthyridine ALLINI compound 23 remained active against such strains (207).…”
Section: Hiv-1 Resistance To Allini Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…242). Because Asn is often found at position 124 and A124D conferred significant resistance to the quinoline ALLINI BI-D (165), recent studies have tested antiviral activities of compounds against HIV-1 strains harboring representative 124/125 polymorphisms, such as Thr/Thr, Thr/ Ala, Ala/Thr, Ala/Ala, Asn/Thr, and Asn/Ala (200,207,215). Whereas Asn-124 and Ala-125 each conferred ϳ50-fold resistance to pyridine ALLINI compound 20 (200) and thiophene ALLINI MUT-A (215), respectively, naphthyridine ALLINI compound 23 remained active against such strains (207).…”
Section: Hiv-1 Resistance To Allini Compoundsmentioning
confidence: 99%
“…On the flip side, thiophene ALLINI MUT-A efficiently inhibited LEDGF/p75 binding to Ala-125containing IN yet in large part lost the ability to hypermultimerize this polymorphic variant. In this case, downstream interactions of the CCD-engaged ALLINI with the CTD of another IN oligomer seemed to underlie the loss of hypermultimerization activity (215). Thus, resistance to ALLINIs can be instilled by loss of direct IN binding contact, a shift in compound position within the CCD-binding pocket, or inability of bound compound to mediate downstream interactions.…”
Section: Hiv-1 Resistance To Allini Compoundsmentioning
confidence: 99%
“…Later it was found that LEDGINs also inhibit late stage replication (the so-called 'late effect' , Fig. 1) [63][64][65][66][67][68]. Viral particles produced in the presence of LEDGINs display morphological defects due to LEDGIN-induced IN multimerization [63][64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%
“…A hallmark morphological defect of these viruses is the formation of aberrant viral particles with viral ribonucleoprotein (vRNP) complexes mislocalized outside of the conical CA lattice [11, 15, 2123, 2628]. Strikingly similar morphological defects are observed in virions produced from cells treated with allosteric integrase inhibitors (ALLINIs, also known as LEDGINs, NCINIs, INLAIs or MINIs) [26, 27, 48-55]. ALLINIs induce aberrant IN multimerization in virions by engaging the V-shaped pocket at the IN dimer interface, which also provides a principal binding site for the host integration targeting cofactor lens epithelium-derived growth factor (LEDGF)/p75 [50, 54, 5660].…”
Section: Introductionmentioning
confidence: 99%
“…The structural basis for IN binding to RNA is not yet known; however, in vitro evidence indicates that IN binds RNA as lower-order multimers, and conversely RNA binding may prevent the formation of higher order IN multimers [28]. Notably, aberrant IN multimerization underlies the inhibition of IN-RNA interactions by ALLINIs [28] and subsequent defects in virion maturation [26-28, 48, 49, 51-55]. Therefore, it seems plausible that class II IN substitutions may exert their effect on virus replication by adversely affecting functional IN multimerization.…”
Section: Introductionmentioning
confidence: 99%